2019
DOI: 10.1007/s00268-019-05206-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Osteopenia in Patients Who Underwent Living Donor Liver Transplantation for Hepatocellular Carcinoma

Abstract: Background Osteopenia, loss of bone mineral density (BMD), was recently identified to be independently associated with early marker of deconditioning that precedes sarcopenia in patients with hepatocellular carcinoma (HCC). The aim of this study was to clarify the impact of osteopenia as the risk factor for mortality after living donor liver transplantation (LDLT) compared with already‐reported biological markers. Methods Data were collected retrospectively for all consecutive patients who underwent LDLT for H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 35 publications
3
37
3
Order By: Relevance
“…Interestingly, in this study, there was no significant difference in the disease-free survival between the patients with and without osteosarcopenia. Toshima et al and Sharma et al also demonstrated that osteopenia was independently associated with post-liver transplantation survival in HCC patients, but not recurrence 15,13. They pointed out how effective treatments for recurrence were done might be related to osteopenia; however, the present study showed appropriate diagnostic cutoff values.…”
contrasting
confidence: 52%
See 2 more Smart Citations
“…Interestingly, in this study, there was no significant difference in the disease-free survival between the patients with and without osteosarcopenia. Toshima et al and Sharma et al also demonstrated that osteopenia was independently associated with post-liver transplantation survival in HCC patients, but not recurrence 15,13. They pointed out how effective treatments for recurrence were done might be related to osteopenia; however, the present study showed appropriate diagnostic cutoff values.…”
contrasting
confidence: 52%
“…Inflammatory conditions, nutritional factors, and aging have been postulated as the molecular mechanism. On the other hand, there are few reports to show the prognostic value of osteopenia 13,15 . It is not clear whether the bone loss promotes cancer development or whether stable bone density prevents cancer invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After contacting the original authors, we included an additional study. Finally, 11 studies (2230 patients) were included for the meta-analysis [23][24][25][26][27][28][29][30][31][32][33].…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows the characteristics of the included studies [23][24][25][26][27][28][29][30][31][32][33]. Of the 11 studies, three studies focused on pancreatic cancer [25,26,28], two on colorectal liver metastases [29,30], two on extrahepatic cholangiocarcinoma [24,32], one on esophageal cancer [31], one on colon cancer [33], and two on hepatocellular carcinoma [23,27]. Six studies adopted cutoff values for BMD from previous studies [23,25,33,[27][28][29], while the other five studies adopted their own cutoff values [24,26,[30][31][32].…”
Section: Resultsmentioning
confidence: 99%